Chemiluminescence from Ozonized Sesame Oil - Pavan, Nathalia Mariana [UNESP]; Passaretti Filho, Juliano [UNESP]; Isquibola, Guilherme [UNESP]; Caires, Flávio Junior [UNESP]; Ximenes, Valdecir Farias [UNESP] (Taylor & Francis, 2022)
The applications of ozonized oils in human medicine, veterinary, and dentistry have been experiencing a significant increase in the last years. An important chemical property of ozonized oils is their oxidizing capacity, which is directly related to the therapeutical effects. This work aimed to study the light emission caused by the oxidation of luminol by ozonized sesame oil. Sesame oil was ozonized at different time intervals and characterized by peroxide index, Fourier-transform infrared spectroscopy, and thermal analysis. The light emission efficiency was correlated with the pH of the medium, the concentration of horseradish peroxidase (HRP), used as a catalyst, and solvents. A linear correlation was obtained between the concentration of ozonized oil and the integrated light emission. In a second approach, taurine chloramine (Tau-NHCl) was used instead of HRP. The light emission was dependent on both ozonized oil and Tau-NHCl, showing the involvement of intermediate oxidative species in the reaction. Considering the growing therapeutic applications of ozonized oils and Tau-NHCl, these findings instigate further biological investigations to characterize additive or synergic microbicidal properties.
Keywords: Chemiluminescence; luminol; Ozonized oil; Sesame oil; Taurine chloramine